Unraveling the role of excess ligand in nanoparticle pattern formation from an evaporatively dewetting nanofluid droplet - Bhattacharjee, Kaustav; Biswas, Korak; Bhagavatula L. V. Prasad (Journal of Physical Chemistry C, 2020)
Nanoparticle (NP) patterning on a solid surface via nanofluid droplet evaporation is one of the most fascinating topics of research. Quite intriguingly, though a dose of excess ligand has been invariably included in all of the experimental studies that resulted in large-area NP patterns, the role of this excess ligand has been addressed inadequately in the modeling studies carried out so far. Addressing this, we have conducted systematic studies by including excess ligand both in our experiments and modeling, and correlated the results with each other. For this, we prepared nearly monodispersed thiol-protected gold nanoparticle dispersion in toluene and added calculated amounts of excess thiol before drop-casting it onto a transmission electron microscopy (TEM) grid. Subsequently, upon solvent evaporation, the patterns formed were imaged using conventional electron microscopy and analyzed with customized image processing tools, to perform statistically significant measurements. Our study demonstrates the ability of soluble excess ligand to induce NP aggregation under nonequilibrium condition, leading to large-area monolayer formation. These experimental results were then rationalized by Monte Carlo simulations, based on a modified coarse-grained two-dimensional (2D) lattice-gas model. We found that excess ligand facilitates NP spinodal phase separation under nonequilibrium conditions, largely governed by the interplay between ligand-solvent and nanoparticle-ligand interactions. Using power spectrum density analysis, we clearly demonstrate that these spatial patterns have fractal surface characteristics due to persistent fractional Brownian motion within subdiffusion limit.